Pengaruh Motivasi Kerja, Pelatihan Kerja, dan Stres Kerja Terhadap Kepuasan Kerja pada Karyawan Dinas Pemadam Kebakaran Kabupaten Paser - Nurleni; Didik Hadiyatno; Rahajeng Cahyaning Putri (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The purpose of this study was to determine the effect of Work Motivation, Job Training, and Job Stress on Job Satisfaction of Paser Regency Fire Department Employees. The type of research used is quantitative research. The sampling technique in this study was total / census sampling with a population of 88 employees, so the sample taken was all employees of the Paser Regency Fire Service, totaling 88 employees. The data collection method was carried out by distributing questionnaires. This study uses multiple linear regression with the help of SmartPLS in processing data. The results of this study indicate that the work motivation variable partially affects the job satisfaction of Paser Regency Fire Department employees, the job training variable partially affects the job satisfaction of Paser Regency Fire Department employees, and the job stress variable partially affects the job satisfaction of Paser Regency Fire Department employees.